The small hydrophobic protein of the human respiratory syncytial virus forms pentameric ion channels - Gan, Siok-Wan (2013)
The small hydrophobic (SH) protein is encoded by the human respiratory syncytial virus. Its absence leads to viral attenuation in the context of whole organisms, and it prevents apoptosis in infected cells. Herein, we have examined the structure of SH protein in detergent micelles and in lipid bilayers, by solution NMR and attenuated total reflection-Fourier transform infrared spectroscopy, respectively. We found that SH protein has a single α-helical transmembrane domain and forms homopentamers in several detergents. In detergent micelles, the transmembrane domain is flanked N-terminally by an α-helix that forms a ring around the lumen of the pore and C-terminally by an extended β-turn. SH protein was found in the plasma membrane of transiently expressing HEK 293 cells, which showed pH-dependent (acid-activated) channel activity. Channel activity was abolished in mutants lacking both native His residues, His22 and His51, but not when either His was present. Herein, we propose that the pentameric model of SH protein presented is a physiologically relevant conformation, albeit probably not the only one, in which SH contributes to RSV infection and replication. Viroporins are short (∼100 amino acids) viral membrane proteins that form oligomers of a defined size, act as proton or ion channels, and in general enhance membrane permeability in the host. However, with some exceptions, their precise biological role of their channel activity is not understood. In general, viroporins resemble poorly specialized proteins but are nevertheless critical for viral fitness. In vivo, viruses lacking viroporins usually exhibit an attenuated or weakened phenotype, altered tropism, and diminished pathological effects. We have chosen to study the SH protein, 64 amino acids long, found in the human respiratory syncytial virus because of the effect of RSV on human health and the lack of adequate antivirals. We show that SH protein forms oligomers that behave as ion channels when activated at low pH. This study adds SH protein to a growing group of viroporins that have been structurally characterized. Although the precise biological role of this pentameric channel is still unknown, this report is nevertheless essential to fill some of the many gaps that exist in the understanding of SH protein function.